15 TRICHOBEZOAR AND ACUTE ABDOMEN. (1st March 2007) - Sapkota, R. P.
Abstract : Background: Trichobezoar is defined as a foreign body composed of hair found in the stomach and rarely in the intestine. The first description of human trichobezoar was in 1779. More than 90% of human trichobezoar occurs in young females, often with a history of some mental illness. The bezoar may cause a mechanical obstruction of the gut. This is especially true in the stomach, where the pyloric could be blocked; clinical manifestations include abdominal pain, epigastric distress, nausea, vomiting, and fullness. Case Report: A 21-year-old female with a history of mental illness was brought to the emergency department of Coney Island Hospital on November 5, 2006. The patient presented with abdominal pain, which started 1 day prior to admission but worsened in the last 2 to 3 hours prior to admission, nausea, and multiple episodes of vomiting. The patient denied diarrhea, fever, urinary problems, and any abdominal pain or discomfort previously. She was not taking any medication; she wears an IUD contraceptive and had also had 2 to 3 days of vaginal bleeding. On physical examination, she was acutely ill looking, blood pressure was 130/90 mm Hg, pulse was 90/min, temperature was 97.8°F, and respiration was 22/min; she appeared to be dehydrated. There were no signs of trauma. The chest and cardiovascular system were normal, and an abdominal examination was remarkable for BS present, very tender, gardening, and a palpable hard mass in the the epigastric area and left upper quadrant and umbilical area. Stool guaic was negative. Gastric lavage was unrevealing. A transvaginal US by GYN was normal. Laboratory tests were β-HCG negative, WBC 24.0, Hgb 9.6, MCV 67.1, Plt 503, SEG 95, Na 135, K 4.0, CL 101, CO2 20, BUN 9, Creat 0.7, Ca 10.1, total P 7.5, Alb 4.7, Alk phos 44, AST 25, ALT 18, PT 13.8, INR 1.4, and aPTT 21.9. Plain abdominal radiography showed gastric dilatation. Abdominal CT showed gastric dilatation with bezoars versus food material with large intramural air collection at the greater curvature with adjacent intraperitonum air collection and possible perforation at the antrum of the stomach and large intraperitoneal fluid collection. The patient was scheduled for emergent surgical exploration, which found trichobezoars. Biopsy showed polypoid edematous gastric mucosa with trichobezoar. A liquid diet was started on the fourth day, and she was discharged after 25 days. Postoperative upper gastrointestinal endoscopic studies did not reveal any inflammation in the stomach. She was referred for psychiatric consultation and 6 months of follow-up. Conclusionand Discussion: Bezoars are masses of solidified organic and inorganic biologic material commonly formed in the stomach and small bowel. The major types are phytobezoars, trichobezoars, pharmacobezoars, lactobezoars, and miscellaneous. Trichobezoars, composed of hair, usually occur in young women with psychiatric disorders. Trichotillomania (hair pulling) and trichophagia (hair eating) usually precede trichobezoar formation. The ingested hairs in the stomach form a hairball, the interstices of which get entangled by vegetable fibers, and the stomach is unable to push this mass forward. Sometimes the gastric trichobezoar fragments into pieces, which then pass into the intestine and at times may cross the ileocecal junction. Affected patients remain asymptomatic for many years and develop symptoms insidiously, usually present with nausea, vomiting, vague abdominal pain, mass, weight loss, anemia, jaundice, pancreatitis, and bowel obstruction.